Colors & Effects introduces new Spectrasense pigments brand, certified colorants portfolio. Issue 12 (December 2020) - Unknown
Abstract : The Colors & Effects® brand of BASF [ see also page 4 ] has announced its new Spectrasense™ line of innovative functional pigments, delivering functionality beyond the coloristic properties of a pigment, in particular for enabling management of near-infrared (NIR) wavelengths for modern technologies in various applications. Colors & Effects has also introduced a dedicated pigment portfolio for sustainable fibre coloration, which meets performance requirements for various polymers as well as high purity standards set by Oeko-Tex®.